MIMO Exploitation of 3D Multipath Statistics in a Heterogeneous LTE-Advanced Network - Zuhanis Mansor; Evangelos Mellios; Geoffrey Hilton; Joe McGeehan; Andrew Nix (International Journal of Antennas and Propagation)
This paper analyses the impact of 3D multipath in an LTE-Advanced heterogeneous network. The impact of the base station array configuration is considered in both the azimuth and elevation planes. Spatial and temporal multipath statistics are generated for example macro- and picocellular base stations, and these are combined with appropriately oriented complex polarimetric antenna patterns. The resulting wideband channels are then passed to an LTE-Advanced physical layer simulator. The optimal spatial multiplexing mode is determined by computing the throughput using the received bit mutual information rate for all modulation and coding schemes. The fastest link speed for each user is identified given a packet error rate threshold of 10%. Results show that RMS angle spread statistics and the base station MIMO array configuration strongly influence user performance in an LTE-A network. The deployment of macrocellular vertical arrays is shown to significantly degrade network performance. In contrast, the elevation angle spread is found to be far greater in picocells, and this allows vertical arrays to be applied to produce compact high performance picobase stations.